Concept development of an integrated rear-facing child seat structure - Sumant, Abhijit; Dawkare, Swapnil (My University, 2024)
This Master of Science (MSc) thesis project aims to develop a concept for rearfacing child seat structures. It was conducted in collaboration with Volvo cars and explores a new child seat and safety product design approach, differentiating from traditional front-facing integrated child seat design. The project’s uniqueness lies in its approach to seamlessly integrating child safety within the standard adult seat, simplifying the operation and ensuring optimal safety for young passengers. Product development methods and techniques such as literature study, data gathering, needs and requirement analysis, concept selection, product architecture, concept design, product analysis, and design validation are used to achieve the goal. The above process resulted in a functional concept of rearward-facing integrated child seats with different operational mechanisms. The product meets the user and technical requirements derived from the qualitative data research. It is important to note here that the product is verified for the requirements and not validated due to limitations such as a compact timeline, lack of expertise in FEM and lack of resources. In conclusion, our team has prepared a baseline for further advanced product development and contributed to establishing a way forward in reducing the time during design improvements and analysis. .